pengaruh PENGARUH LINGKUNAN KERJA TEHADAP PRODUKTIVITAS KINERJA PEGAWAI PADA WARTEG RIZKY 24 JAM : Lingkungan kerja - Lumban Siantar, Petrus Bekam (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
Work productivity is one of the important factors in achieving organizational goals. Productive employees will produce more output with good quality in less time. This will certainly have a positive impact on organizational performance and profits. Work environment is one of the factors that can affect employee productivity. A conducive and comfortable work environment can increase the enthusiasm and motivation of employees to work more actively and productively. Conversely, a work environment that is not conducive and comfortable can reduce employee enthusiasm and motivation, resulting in decreased productivity. The method that the author uses in this research is direct research going to the location by conducting interviews with owners and employees. The approach used in this research is a qualitative approach to the perpetrator, so that researchers get more information and data that can maximize this research. The results of interviews conducted with owners and employees of risky wartegs are that the work environment affects employee performance. Adequate facilities, a structured work system, appropriate working hours, sufficient wages, and employees who are harmonious with each other make employees comfortable and their performance becomes very productiveThe results of interviews conducted with owners and employees of risky wartegs are that the work environment affects employees.